Effectiveness and Safety of Immunotherapy for Hepatocellular Carcinoma in Clinical Practice: A Brazilian Multicenter Study - Leonardo Gomes da Fonseca; Cecília Souza Freire; Rodrigo Antonio Vieira Guedes; Marcos Castro Lyra; Maria Ignez Freitas Melro Braguiroli; Mariana Bruno Siqueira; Maria De Lourdes Lopes de Oliveira; Alexandre de Mendonça Palladino; Henry Luiz Najman; Rodrigo Tancredi; Duilio Reis Da Rocha Filho; Markus Cavalcante Gifoni; et al. (JCO Global Oncology)
PURPOSEImmunotherapy-based combinations have shown promising survival benefits in patients with hepatocellular carcinoma (HCC) included in clinical trials. However, real-world data are needed to assess the effectiveness and safety of these therapies in diverse clinical settings and regions.PATIENTS AND METHODSWe conducted a Brazilian multicenter observational study, including 163 patients with unresectable or metastatic HCC treated with immunotherapy between August 2020 and March 2024 in 14 centers. Patient characteristics, treatment outcomes, and adverse events were analyzed. Survival outcomes were assessed using the Kaplan-Meier method, and Cox regression identified predictors of survival.RESULTSMost patients were male (85.3%), with a median age of 72 years. Liver cirrhosis was present in 70.6%, and 77% had Barcelona Clinic Liver Cancer stage C. Immunotherapy was predominantly first-line (91.4%), with atezolizumab plus bevacizumab as the most common regimen (77.9%). The median treatment duration was 4.9 months, and the median overall survival (OS) was 14.7 months (95% CI, 11.6 to 24.5), with 12- and 24-month survival rates of 57.0% and 41.4%, respectively. Considering the patients with Child-Pugh A and performance status 0-1 (n = 116), the median OS was 20.6 months (95% CI, 12.4 to 25.8). Immune-related adverse events occurred in 19.6%, mainly thyroid disorders and skin manifestations. Adverse events related to bevacizumab included variceal (n = 6) and other bleeding events (n = 7). Albumin-bilirubin grade 2 to 3, metabolic dysfunction–associated steatotic liver disease, and esophagogastric varices were independently associated with reduced OS.CONCLUSIONIn a real-world setting, immunotherapy-based treatments demonstrated effectiveness and safety profiles consistent with clinical trials, although survival was influenced by liver function, etiology, and baseline variceal status. These findings highlight the relevance of baseline liver disease characteristics in guiding immunotherapy in HCC and underscore the need for tailored management strategies.